2018
DOI: 10.2478/pjmpe-2018-0010
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of jaws-only intensity modulated radiation therapy treatment plans using Octavius 4D system

Abstract: Introduction: Jaws-Only Intensity modulated radiation therapy (JO-IMRT) is a technique uses the collimator jaws of the linear accelerator (LINAC) to delivery of complex intensity patterns. In previous studies, pretreatment patient specific quality assurance for those JO-IMRT were also performed using ionization chamber, MapCHECK2, and Octavius 4D and good agreements were shown. The aim of this study is to further verify JO-IMRT plans in 2 different cases: one with the gantry angle set equal to beam angle as in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The QA is very important to consider the feasibility of the application of this technique before treatment. 25 Our measurements showed that the dose distributions planned using IMRT TPS are accurate and suitable for treatment delivery. It is interesting to note that all 20 plans of this study passed the requirements based on our established pass criteria (γ-index criterion of 3%/3 mm and pass rates of 96•65 ± 0•86%).…”
Section: Discussionmentioning
confidence: 71%
“…The QA is very important to consider the feasibility of the application of this technique before treatment. 25 Our measurements showed that the dose distributions planned using IMRT TPS are accurate and suitable for treatment delivery. It is interesting to note that all 20 plans of this study passed the requirements based on our established pass criteria (γ-index criterion of 3%/3 mm and pass rates of 96•65 ± 0•86%).…”
Section: Discussionmentioning
confidence: 71%
“…The maximum dose for the brain stem and spinal cord [33,34] and the mean dose for the parotids [35][36][37][38] were not statistically significant for either 7-field or 9-field IMRT (p > 0.05). The NTCP [39], effective volume, EUD, and NTID of the brainstem, spinal cord, and parotids were also not statistically significant (p > 0.05).…”
Section: Comparisons Of Oar With Imrt (7 Fields and 9 Fields)mentioning
confidence: 84%